Penerapan Vaksin Booster Covid-19 dan Teknik Protokol Kesehatan dalam Rangka Pencegahan Virus Corona pada Jemaatdoktujuh - Frans Simbol Tambing; Bodian Davin Panggabean (Fakultas Teknik Universitas Cenderawasih, 2024)
Administering advanced doses of the Covid-19 vaccine (booster) to the public will provide longer protection against the corona virus. The benefits of booster vaccines from a health perspective have at least 3 important reasons. First, there has been a tendency for the number of antibodies to decrease since 6 months after vaccination, especially amid the emergence of new Covid-19 variants including the Second Omicron variant, as a form of effort to adapt people living during the Covid-19 pandemic for long-term health. And third, fulfilling the right of every Indonesian to access vaccines for self and community protection.Some people have complied with health protocols, but there are still others who lack the awareness to apply the 5M principles, namely wearing masks, washing hands, maintaining distance, avoiding crowds, and reducing mobility. Everyone must be willing and able to make changes in 5M compliance behavior, so as to prevent the transmission of Covid-19. The Devotion Team and church servants always remind all members of the congregation to remain disciplined in complying with health protocols and supporting the government's efforts to break the chain of distribution of Covid-19. One of the efforts that can be used to stop the transmission of Covid-19 is by administering the covid-19 vaccine and booster vaccines, using PPE, washing hands, and keeping a distance.The result of this service activity is that all members of the dock seven congregation and its surroundings will receive a complete vaccine starting from vaccines 1, 2, booster 1, and booster 2 so that an immune system and clinical protection are achieved as an effort to maintain long-term health.